2020
DOI: 10.3390/en13071750
|View full text |Cite
|
Sign up to set email alerts
|

Space Charge Accumulation at Material Interfaces in HVDC Cable Insulation Part II—Simulations of Charge Transport

Abstract: Extruded high voltage direct current (HVDC) cable systems contain interfaces with poorly understood microscopic properties, particularly surface roughness. Modelling the effect of roughness on conduction in cable insulation is challenging, as the available results of macroscopic measurements give little information about microscopic charge distributions at material interfaces. In this work, macroscopic charge injection from interfaces is assessed by using a bipolar charge transport model, which is validated ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…The first TSDC peak was systematically observed around T g for all the films (trap depth ∼0.75 eV). For the silica compounds however, the TSDC spectra above T g became more pronounced and complex, indicating higher presence of shallow (or rather, “inter-level” 87 ) traps with trap depths in the 0.7–0.9 eV range in comparison to neat BOPP. In the high temperature region (∼90 °C and above), the unfilled BOPP films exhibited strong TSDC peaks corresponding to charges released from deep traps (in the range of 1.1–1.3 eV), often being anomalous in the sense that the current flow was in the same direction as the polarization current (polarity reversal) which is a result from drifting of thermally de-trapped charge under the internal field caused by the space charge.…”
Section: Resultsmentioning
confidence: 96%
“…The first TSDC peak was systematically observed around T g for all the films (trap depth ∼0.75 eV). For the silica compounds however, the TSDC spectra above T g became more pronounced and complex, indicating higher presence of shallow (or rather, “inter-level” 87 ) traps with trap depths in the 0.7–0.9 eV range in comparison to neat BOPP. In the high temperature region (∼90 °C and above), the unfilled BOPP films exhibited strong TSDC peaks corresponding to charges released from deep traps (in the range of 1.1–1.3 eV), often being anomalous in the sense that the current flow was in the same direction as the polarization current (polarity reversal) which is a result from drifting of thermally de-trapped charge under the internal field caused by the space charge.…”
Section: Resultsmentioning
confidence: 96%
“…Simulations have been performed in the presence of a surface roughness at the anode only. Previous studies [3,5] have shown that concave defects increase the local electric field to a larger extent. To account as simply as possible for surface roughness, protusions having an elliptic shape have been simulated on a length of 10µm at the anode.…”
Section: A Surface Roughnessmentioning
confidence: 83%
“…Charges, generated at the electrodes or inside the bulk, disturb the electric field distribution, leading to local field enhancements, and potentially to an early breakdown. Bipolar charge transport models, also called BCT or mesoscopic models [1][2][3], have been developed this last two decades to predict the electric field distribution within such insulating materials. Electronic charges generation (electrons or holes) at the electrodes are generally described as charge injection, either using the thermionic -i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern methodologies for the simulation of electric fields in solid dielectrics do not consider polarization processes, but focus on bipolar charge transport (BCT) models (see, for example, [14][15][16][17]). These models describe the motion of two charge carriers (electrons and holes) through the bulk of the dielectric by means of the drift-diffusion equations.…”
Section: Introductionmentioning
confidence: 99%